2022
DOI: 10.3389/fenvs.2022.1089517
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions and economic growth in the Yellow River Basin: Decoupling and driving factors

Abstract: In the context of global countries’ pursuit of sustainable development and “dual carbon” goals of China, this paper combines the Tapio decoupling model, Kaya’s equation and LMDI decomposition method to analyze the relationship between carbon emissions and economic growth and the driving factors of carbon emissions in the Yellow River Basin (YRB) of China from 2001 to 2019. It is found that the decoupling state of CO2 and economic growth in the Yellow River Basin shows a trend of expansion negative decoupling -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Energy-related data were acquired from the "China Energy Statistical Yearbook" and the "Statistical Bulletin of National Economic and Social Development (2010-2019)" for each city. Urban carbon emissions and carbon sequestration data were based on relevant literature [49][50][51] from 1997 to 2017. Other than that, the time series model was optimally selected using the SPSS expert modeler, and was finally predicted by the ARIMA model and the Brownian model, with the goodness of fit exceeding 97.5%.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Energy-related data were acquired from the "China Energy Statistical Yearbook" and the "Statistical Bulletin of National Economic and Social Development (2010-2019)" for each city. Urban carbon emissions and carbon sequestration data were based on relevant literature [49][50][51] from 1997 to 2017. Other than that, the time series model was optimally selected using the SPSS expert modeler, and was finally predicted by the ARIMA model and the Brownian model, with the goodness of fit exceeding 97.5%.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Liu et al, Zhao et al, and Gu et al used the STIRPAT model to verify the significant effect of industrial structure transformation and upgrades on reducing carbon emissions [10][11][12]. Developing the Tapio decoupling model, Kaya's equation and LMDI decomposition method, Han et al [13] found that the industrial structure and energy structure effect play negative roles in driving carbon emissions. The degree of coupling coordination among industrial structure, carbon emissions, and the regional innovation of Shandong Province were calculated, and their spatial characteristics and the aggregation effects of both coupled and coordinated development were explored by Wang et al [14].…”
Section: Literature Review and Research Hypotheses 21 Literature Reviewmentioning
confidence: 99%
“…Currently, climate change caused by greenhouse gases is harmful to human survival and sustainable economic development, and controlling greenhouse gas emissions, such as carbon dioxide, has become a global consensus [1]. China has consistently held the title of the world's foremost emitter since 2007.…”
Section: Introductionmentioning
confidence: 99%
“…After endogenous treatment, rigorous robustness checks, and heterogeneity analysis, the study delves into mediation mechanisms, which encompass the livestock industry scale effect, technology innovation effect, and factor allocation effect. The potential contributions of this study are as follows: (1) it extends the research on the environmental effects of NIC to the field of livestock industry. (2) This study concludes that NIC can suppress LCEs, providing policy references for the coordinated realization of NIC goals and dual-carbon targets.…”
Section: Introductionmentioning
confidence: 99%